Relación entre los ingresos públicos y la ejecución de gastos públicos de la Municipalidad Distrital de San Juan Bautista periodo 2015-2024 - Ortiz Davila, Vianka Melissa (2025)
This research aimed to determine the relationship between public revenue and public expenditure execution of the local government of the district of San Juan Bautista during the period 2015-2024. Its relevance lies in contributing to the field of public finance and local economics by exploring the principles and dynamics that govern public finance at the local government level and deepening the understanding of the socioeconomic mechanisms that influence local tax collection and, consequently, the execution of public expenditure. After conducting quantitative and correlational research and analyzing the behavior of both variables for forty consecutive quarters, it is inferred that there is a weak direct relationship of 31.67% between public revenue and public expenditure execution of the local government of the district of San Juan Bautista from the first quarter of 2015 to the fourth quarter of 2024. In addition, significant relationships were found between revenue and expenditure in the sources of financing by directly collected resources and by determined resources.